1992
DOI: 10.1097/00003446-199208000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noise and Noise Suppression on Speech Perception by Cochlear Implant Users

Abstract: The recognition of phonemes in consonant-vowel-consonant words, presented in speech-shaped random noise, was measured as a function of signal to noise ratio (S/N) in 10 normally hearing adults and 10 successful adult users of the Nucleus cochlear implant. Optimal scores (measured at a S/N of +25 dB) were 98% for the average normal subject and 42% for the average implantee. Phoneme recognition threshold was defined as the S/N at which the phoneme recognition score fell to 50% of its optimal value. This threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 11 publications
(14 reference statements)
0
64
0
1
Order By: Relevance
“…If the noise reduction algorithm could accurately estimate the noise spectrum, the within-channel SNR is improved in the processed signal. Several research groups have implemented the spectral subtraction noise reduction algorithm and reported improved speech recognition scores for CI users ͑Weiss, 1993; Hochberg et al, 1992;Goldsworthy, 2005͒.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the noise reduction algorithm could accurately estimate the noise spectrum, the within-channel SNR is improved in the processed signal. Several research groups have implemented the spectral subtraction noise reduction algorithm and reported improved speech recognition scores for CI users ͑Weiss, 1993; Hochberg et al, 1992;Goldsworthy, 2005͒.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Audallion BEAMformer that summed the inputs from two directional microphones worn in the implanted ear and in the contralateral ear was reported to have limited benefit on localizing the source of sounds ͑Figueiredo et al, 2001͒, limited directional effects ͑Goldsworthy, 2005͒, and limited acceptability among CI users. In addition, several groups of researchers have reported positive findings using spectral subtraction noise reduction algorithms to enhance the speech recognition of CI users in background noise ͑Hochberg et al, 1992;Weiss, 1993;Goldsworthy, 2005͒. The computational demand, however, prevents such algorithms from being implemented in wearable CIs.…”
Section: Introductionmentioning
confidence: 99%
“…However, when listening conditions are less favorable, implant users may encounter much greater difficulty than their normal-hearing counterparts. For example, even small amounts of background noise can cause implant listeners to experience substantial reductions in speech recognition (Fu, Shannon, & Wang, 1998;Hochberg, Boothroyd, Weiss, & Hellman, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, speech performance deteriorates rapidly with increased levels of background noise, even for the best CI users. Understanding CI users' susceptibility to noise remains a major challenge for researchers (e.g., Dowell et al 1987;Hochberg et al 1992;Kiefer et al 1996;Mü llerDeiler et al 1995;Skinner et al 1994), and is an important step toward improving CI users' performance in noisy listening conditions. Recent innovations in electrode design and speech processing have helped to improve CI users' performance in noise (Skinner et al 1994;Kiefer et al 1996).…”
Section: Introductionmentioning
confidence: 99%